MODUL DIGITAL ADAPTIF MATEMATIKA SEBAGAI SOLUSI UNTUK KEANEKARAGAMAN KEMAMPUAN BELAJAR - Setiawan, Rudy; Wijaya, Elita Mega Selvia; Anwar, Moh. Farid Nurul (Universitas Insan Budi Utomo, 2025)
This study examines the effectiveness of adaptive digital modules in addressing the diversity of learning abilities of students in Elementary School Teacher Education (PGSD) classes. The background of this study focuses on the challenges faced by students with varying levels of ability in learning mathematics. The purpose of this study is to develop and evaluate adaptive digital modules that can adjust learning materials to the needs of individual students. The research method used was a quasi-experiment including module development, trials in several PGSD classes, and data collection through pre-tests, post-tests, and satisfaction surveys. The results showed that the use of adaptive digital modules significantly improved understanding of mathematical concepts, motivated students, and accommodated various learning styles. This module succeeded in reducing disparities in learning outcomes and increasing student engagement. The conclusion of this study is that adaptive digital modules are an effective solution for diversity of learning abilities so that they can improve the quality of learning in PGSD classes.